Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS de la Côte-Nord - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

A Study of Women's Needs on the Lower North Shore - Keats, Shannon A. (Coasters Association, 2006)
The mission of the Coasters Association is to develop knowledge of the needs and expectations of the fourteen (14) communities on the Lower North Shore, and act in partnership with community leaders, organizations and stakeholders to design and deliver community strategies, programs and services which respond to the region’s development challenges. In keeping with their mission and providing an opportunity to better the situation of women on the Lower North Shore, a project entitled “A Study of the Needs of Women on the Lower North Shore”, was initiated. The project began on the September 12th, 2005 and ended on March 31st, 2006 (29 weeks). The key goal of the project was to get women involved and talk about the issues facing them and to identify opportunities and lasting solutions, as well as make women aware of the programs and services that are available on the coast, through partnerships with other organizations and to help these women make use of those programs. The purpose of the project was to research information through means of a questionnaire and by organizing focus groups to develop a needs assessment and to establish a coalition (for Phase 2 of the project) to improve the overall status of women on the Lower North Shore of Quebec.